Peran kelekatan dengan orangtua dan kecerdasan emosional terhadap kesejahteraan psikologis siswa SMA - Yundari, Aristi Dwi; Nurcahyo, Firmanto Adi (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2023)
Psychological well-being is a condition when the individual is not under stress or other mental health problems. The existence of psychological well-being can improve the adolescents mental health and help the adolescents function optimally. Proper consideration is needed for the psychological well-being of adolescents to be enhanced. The factors to consider include parent attachment and emotional intelligence. This study is a quantitative study to determine the role of parent attachment and emotional intelligence for the psychological well-being of high-school student. A total of 165 students of class X, XI, and XII at one of the state high schools in Denpasar were the respondents in this study using stratified random sampling. Psychological Well-Being Scale with a reliability of 0,915, the Parent Attachment Scale with a reliability of 0,935, and a Scale of Emotional Intelligence with a reliability of 0,845 as the measurement tools that used. The multiple regression test revealed F=41,808, p<0,05, indicating that parent attachment and emotional intelligence characteristics both contribute to psychological well-being. Parent Attachment and emotional intelligence jointly contribute 33,2% to psychological well-being. Based on these, students are strongly advised to maintain relationships with parents and to increase their emotional intelligence, to help increase their psychological well-being possessed.